1974
DOI: 10.1139/m74-156
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of pigmentation mutants of Micrococcus roseus

Abstract: A number of UV-induced pigmentation mutants of Micrococcus roseus were isolated. The carotenoid pigment composition of a yellow mutant and a pink mutant were determined and compared with the composition of the wild type. The yellow mutant appeared to have the ability to insert oxygen functions on only one end of β-carotene. The pink mutant formed less total carotenoids than the wild type; it formed diketo-carotenoids but no dihydroxy compounds. The results are discussed in relation to xanthophyll synthesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
12
1
Order By: Relevance
“…In M. roseus, however, carotenoids do not appear to protect the cells from photodynamic killing (29). In fact, cells of M. roseus in which carotenoid biosynthesis was stopped with diphenylamine showed very small amounts of carotenoids but exhibited greater resistance to photodynamic killing than did the pigmented wild-type M. roseus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In M. roseus, however, carotenoids do not appear to protect the cells from photodynamic killing (29). In fact, cells of M. roseus in which carotenoid biosynthesis was stopped with diphenylamine showed very small amounts of carotenoids but exhibited greater resistance to photodynamic killing than did the pigmented wild-type M. roseus.…”
Section: Discussionmentioning
confidence: 97%
“…For M. luteus, it was found to be a dihydroxy C50 carotenoid (35)(36)(37), and for M. roseus the pigments were found to be mainly a or 1B carotene derivatives, with canthaxanthin as the main pigment (3,28,38). Studies have indicated that carotenoids in M. roseus do not protect the bacterium against photodynamic killing (29).…”
mentioning
confidence: 99%
“…Radiation effects observed in Micrococcus using toluidine blue as an exogenous photosensitizer are not comparable with the results presented here [25]. In Myxococcus xanthus carotenoid functions are related with an unusual accumulation of porphyrin [5], and in Micrococcus roseus ATCC 516 [6], at present classified as Kocuria rosea [19], photoprotection is provided by canthaxanthin, echinenone, 4-hydroxyechinenone, and other pigments with a β,β-carotene structure [26], which are structurally different from those found in RMB40. Sarcina lutea ATCC 9341 [3,4] was classified as Micrococcus luteus in 1977, but it was re-classified as Kocuria rhizophila in 2003 [27] and its pigments have not been characterized.…”
Section: Protective Effect Of Carotenoidsmentioning
confidence: 65%
“…However, responsible enzymes for the formation of astaxanthin metabolites and their biological functions have not been elucidated. Canthaxanthinis another keto-carotenoid pigment found in green algae, bacteria, crustaceans and fish (Schwartzel & Cooney, 1972). Tyczkowski, Yagen, and Hamilton (1988) revealed that a portion of canthaxanthin was reduced to 4-hydroxyechinenone (4-hydroxy-4 0 -keto-beta, beta-carotene) that in turn was reduced in part to isozeaxanthin (4,4 0 -dihydroxy-beta,beta-carotene) was confirmed by high performance liquid chromatography analysis of tissues from chicks.…”
Section: Metabolism Of Oxygenated Carotenoidsmentioning
confidence: 88%